436 Collaboration multiplier: advancing multi-sector partnerships to prevent violence. (1st September 2016) - Cohen, Larry; Davis, Rachel
Abstract : Background: Violence poses a serious health challenge, and leads to death, injury and chronic disease. Given the range and complexity of the factors that increase or reduce the likelihood of violence, no single agency can prevent violence on its own. However, it can be challenging to harness the diverse skills, expertise, and assets of so many groups with distinct perspectives and goals. Objective: This session describes how the Collaboration Multiplier tool supports interdisciplinary approaches that prevent violence and can help coalitions overcome obstacles. Presenters will suggest techniques for recruiting different sectors, describe each sector's unique contributions, and share examples of how Collaboration Multiplier has been applied to expand local partnerships that comprehensively address violence affecting young people and communities. Results: The Collaboration Multiplier tool has a long track record of success, and Prevention Institute has used it to facilitate diverse groups for more than a decade. To adapt this tool for preventing violence, Prevention Institute conducted a literature review, a scan of municipal websites, and nearly 40 in-depth interviews with practitioners in the U.S. The resulting publication describes the roles and unique contributions of 10 public and private sectors and 12 municipal departments as they relate to preventing violence and features case examples, talking points to persuade others to get involved, and activities for each step of the Collaboration Multiplier tool. Conclusions: Increasingly, practitioners recognise the value of interdisciplinary approaches, and Collaboration Multiplier can serve as the bridge between various sectors that traditionally work in silos. When people collaborate to address the risk and resilience factors for violence, they can accomplish ambitious goals and have an impact that no organisation could achieve through a stand-alone effort.